Crop weather simulation model in tomato (solanum lycopersicum L.) - Navyasree, S (Department of Agricultural Meteorology, College of Horticulture, 2018)
Tomato (Solanum lycopersicum L.) is known as protective food because of its special nutritive value and wide spread production. Planting time is one of the most important factors among the various cultural practices followed for the production of tomato that greatly influence its growth and yield. Weather parameters play an important role in the growth and yield of tomato. The crop is sensitive to both low and high temperatures. Moisture stress is one of the major problems for the cultivation of tomato, which affects the production adversely. Hence much attention has to be paid on the use of soil cover. The present investigation “Crop weather simulation model in tomato ( Solanum lycopersicum L.) ” was carried out in the Department of Agricultural Meteorology, College of Horticulture, Vellanikkara during 2017-18, to calibrate the genetic coefficients for tomato using DSSAT CROPGRO-Tomato model and to evaluate the micrometeorological aspects of tomato under different growing environments. The field experiment was conducted at the STCR plot, College of Horticulture, Vellanikkara during September (2017) to March (2018). Split plot design was adopted with six dates of planting viz., 15th September, 1st October , 15th October, 1st November, 15th November and 1st December as the main plot treatments and three types of mulches viz., black top white bottom, white top black bottom polythene, straw mulch and control as the sub plot treatments. The number of replications for the experiment was three. The daily weather parameters like maximum and minimum temperatures, forenoon and afternoon relative humidity, bright sunshine hours, pan evaporation, wind speed, rainfall and number of rainy days were recorded during the entire crop growing period, to determine the crop weather relationship. The daily soil temperature determined during the crop growing period showed increasing trend towards the late plantings, whereas weekly soil moisture showed decreasing trend towards late plantings. Black top white bottom polythene retained highest soil temperature and soil moisture. Soil pH, organic carbon and microbial biomass carbon were found to be lowest in control when compared to mulched plots. The analysis of available nitrogen, phosphorus and potassium showed that, the soil samples taken after the harvest of the crop recorded high soil nutrients compared to initial samples. The available soil nutrients (N, P and K) was does not vary between the dates of planting, whereas mulched recorded more soil nutrients compared to control. The increased availability of available nitrogen and phosphorus in polythene mulched plot due to the optimum soil temperature, optimum soil moisture levels, increased mineralization, reduction in nutrients leaching and lower uptake of nutrients by weeds. The increased availability of available potassium in paddy straw mulched plot might be due to addition of potassium to the soil which is present in the straw. In the present investigation, it is clear that the uptake of plant nutrients (N, P, K) was increased due to the addition of mulches, due to sufficient soil moisture, optimum soil temperature, reduction in nutrients leaching, nutrient utilization and reduction in the weeds competition. The maximum height of the plants was found to be highest during 15th September and lowest during 1st December planting. Plant height was high in the mulched plots when compared to the control. The number of trusses per plant for first three plantings were found to be high, whereas it was low in last two plantings. The number of fruits per plant was high in first four plantings and was lowest in last planting. The plants under black top white bottom polythene recorded highest and control recorded lowest number of fruits per plant. The mean yield of 15th September planting was highest and lowest was recorded in control. Yield was high in plants with black top white bottom polythene and straw mulch and were on par. Low number of weeds were recorded in mulched plots, compared to control. The analysis of correlation between weather and yield parameters showed that with increase in the minimum temperature, relative humidity, rainfall and rainy days, yield increased whereas, with increase in the maximum temperature, wind speed, bright sunshine hours and evaporation the yield decreased. Number of days taken for different phenophases viz., first flowering, fifty percent flowering, first fruiting, fifty percent fruiting, harvesting and total duration decreased towards last planting. The duration of the plants with mulches showed long duration compared to control. The correlation between weather and phenophases was significant. The fruit yield and duration of phenophases were influenced by accumulated growing degree days, heliothermal units and photothermal units. The highest recorded accumulated growing degree days, heliothermal units and photothermal units was during 1st December planting. Hence lower fruit yield and less duration for attaining maturity was observed in last dates of planting. The crop genetic coefficients that influence the occurrence of developmental stages in the CROGRO – Tomato model were calibrated, to achieve the best possible agreement between the simulated and observed values. Predicted yield, phenology and leaf area under different planting dates were reasonably close to the observed values. Thus, the study revealed that there is an influence of mulches on the growth and yield of tomato especially in dry conditions. By modifying the micrometeorological conditions, the yield of the tomato can be enhanced during off season. Crop simulation models are efficient in simulating the growth and yield of tomato.